2019
DOI: 10.1111/wej.12541
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics contamination in tidelands of the Osaka Bay area in western Japan

Abstract: Recently, researchers have been examining the actual state of microplastics contamination in the environment. However, pollution in high biodiversity environments such as tidelands has not been sufficiently investigated. Therefore, to assess the actual level of microplastics pollution therein, we conducted a survey of the tidelands of Osaka Bay in Japan to develop a model that included basins in urban and suburban areas. We quantified the levels of microplastics in the mud from four of Osaka Bay's tidelands an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This cluster is proposed to be a derivative of 'fabric pilling' that commonly occurs in lifestyle textile products (Sillanpaa and Sainio, 2017;Corami et al, 2020). Indeed, a PET cluster morphologically similar to that of this study was discovered in crabs (C. dehaani) from Osaka Bay, Japan (Nakao et al, 2020).…”
Section: Perspective 2: Microplastic Distributions Along the Flow Dir...supporting
confidence: 75%
“…This cluster is proposed to be a derivative of 'fabric pilling' that commonly occurs in lifestyle textile products (Sillanpaa and Sainio, 2017;Corami et al, 2020). Indeed, a PET cluster morphologically similar to that of this study was discovered in crabs (C. dehaani) from Osaka Bay, Japan (Nakao et al, 2020).…”
Section: Perspective 2: Microplastic Distributions Along the Flow Dir...supporting
confidence: 75%
“…The comparative MPs' abundance in the coastal sediment of Maharashtra is compared with other studies across the world listed in Table 1 . The current investigation has shown higher MPs than Kanzakigawa River estuary, Osaka Bay, Japan (Nakao et al, 2020), Puducherry coastal environment (Dowarah & Devipriya, 2019), Baram River estuary, Borneo Island, Malaysia (Choong et al, 2021), Jagir Estuary, Surabaya City, Indonesia (Firdaus et al, 2020), and Guanabara Bay, Brazil (Alves & Figueiredo, 2019) (Table 1), while less contamination was recorded than in the Gulf of Khambhat, Gujarat (Rabari, Patel, Patel, et al, 2023), Charleston Harbor Estuary, South Carolina, USA (Leads & Weinstein, 2019), Rhine Estuary, Netherland (Leslie et al, 2013), Derwent Estuary, Australia (Willis et al, 2017), and the Goa, India (Gupta et al, 2021) (Table 1). The higher MPs that have been observed in the beach sediment indicate a higher rate of anthropogenic pressure in the study area.…”
Section: Resultsmentioning
confidence: 56%
“…In this study, the concentration of MPs in rivers varied significantly depending on the artificial surface area in the sub-basin (p < 0.05). Previous studies demonstrated that the abundance of MPs increases in urbanized areas with respect to sub-urban [38,39], which would explain the higher concentration of MPs found in the Gafos and Lagares rivers compared to the rest of the rivers. These two rivers, among those studied, have the highest proportion of their catchment area urbanized, as can be seen in Figure 1 and in Table 1.…”
Section: Occurrence and Distribution Of Microplastics In Watermentioning
confidence: 91%